Pengaruh Kualitas Produk Dan Citra Merek Terhadap Keputusan Pembelian Dan Dampaknya Pada Kepuasan Pelanggan Produk Kosmetik Wardah Di Cikarang Selatan - Lestari, Dian Alia; Wulandari, Anna (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Customer satisfaction is the collection of feelings and beliefs that people have about their current desires. Customer satisfaction is also an employee's feeling about the work they do. Employee feelings towards work can be interpreted as whether employees feel satisfied, comfortable, safe and at ease in carrying out or completing their work. The aim of this research is to determine the influence of product quality and brand image on customer decisions with customer satisfaction as a mediating variable. This research uses quantitative methods with a sample size of 96 respondents. This research was processed using SmartPLS data processing software and data collection was carried out via Google forms. The results of this research show that product quality has a significant effect on customer decisions, brand image has an effect on customer decisions, product quality has an effect on customer satisfaction as a mediating variable, meanwhile several variables that have no effect include product quality that has no significant effect on customer satisfaction, quality product and customer satisfaction have no effect on customer satisfaction.